Diseño de una Planeación Estratégica en la Industria 4.0 en las Pymes de Puerto Colombia (2022)
As a consequence of the changes that society has had in the last decade, the integration of the processes has been updated to the technological part, all the areas of the organization directly or indirectly influence each other, making its internal system increasingly productive. and efficient, generating more than normal value to be able to compete in the market.